2017
DOI: 10.17987/icfj.v11i0.394
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pulmonary Embolism and Paradoxical Embolism in Patients with Patent Foramen Ovale: to Close or Not to Close…That is the Question!

Abstract: <p>Nowadays, the treatment of patent foramen ovale (PFO) after acute pulmonary embolism (PE) remains matter of speculation. Absence of both randomized trials and recommendations in current international guidelines complicate the decisions making in such patients. In the present manuscript we discuss about the reasons for which PFO should be closed after acute PE.</p>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The optimal management of patients with paradoxical embolism from PFO remains controversial. Zuin et al suggested that for patients with thrombophilia and PFO, the transcatheter closure of PFO, along with chronic oral anticoagulation, is recommended [3]. Data from long-term studies involving large patient populations for percutaneous PFO closure are still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal management of patients with paradoxical embolism from PFO remains controversial. Zuin et al suggested that for patients with thrombophilia and PFO, the transcatheter closure of PFO, along with chronic oral anticoagulation, is recommended [3]. Data from long-term studies involving large patient populations for percutaneous PFO closure are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal management of patients with paradoxical embolism from PFO is challenging. It must be individualized based on the potential benefits and risks considering the patients' comorbidities along with procedural complications [3]. We report an elderly patient who presented with an acute sub-massive PE treated with thrombolytic therapy and had a paradoxical embolism and ischemic stroke as a result of a clot traversing through a PFO.…”
Section: Introductionmentioning
confidence: 99%